CHEMICAL CONSTITUENTS AND PHARMACOLOGICAL ACTIVITIES OF LANTANA CAMARA – A REVIEW - ALI ESMAIL AL-SNAFI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The review was designed to investigate the traditional uses, chemical constituents and pharmacological effects of Lantana camara. Methods: In the current review, databases including Web Science, Pub Med, Scopus and Science Direct, were searched to investigate the chemical constituents and pharmacological effects of Lantana camara. Results: The plant contained alkaloids, glycosides, steroids, saponins, flavanoids, coumarins, tannins, carbohydrates, hydroxy anthraquinones, anthraquinone glycosides, proteins, phytosteroids, fixed oils, fats, and triterpinoids. Previous pharmacological studies revealed that Lantana camara possessed antimicrobial, antiparasitic, anxiolytic, gastrointestinal, hypoglycemic, cardiovascular, antioxidant, anticancer, antiinflammatory, analgesic, wound healing, antiurolithiatic, hepatoprotective, reproductive, anti–hemorrhoidal, thrombin inhibition and many other effects. Conclusion: Lantana camara represents a promising medicinal plant with a wide range of pharmacological activities that could be utilized in several medical applications because of its effectiveness and safety.